The non-canonical BAF chromatin remodeling complex is a novel target of spliceosome dysregulation in SF3B1-mutated chronic lymphocytic leukemia - Hägerstrand, Daniel; Oder, Blaž; Cortese, Diego; Qu, Ying; Binzer-Panchal, Amrei; Österholm, Cecilia; Del Peso Santos, Teresa; Rabbani, Leily; Asl, Hassan Foroughi; Skaftason, Aron; Ljungström, Viktor; Lundholm, August; et al. (Leukemia, 2024)
SF3B1 mutations are recurrent in chronic lymphocytic leukemia (CLL), particularly enriched in clinically aggressive stereotyped subset #2. To investigate their impact, we conducted RNA-sequencing of 18 SF3B1MUT and 17 SF3B1WT subset #2 cases and identified 80 significant alternative splicing events (ASEs). Notable ASEs concerned exon inclusion in the non-canonical BAF (ncBAF) chromatin remodeling complex subunit, BRD9, and splice variants in eight additional ncBAF complex interactors. Long-read RNA-sequencing confirmed the presence of splice variants, and extended analysis of 139 CLL cases corroborated their association with SF3B1 mutations. Overexpression of SF3B1K700E induced exon inclusion in BRD9, resulting in a novel splice isoform with an alternative C-terminus. Protein interactome analysis of the BRD9 splice isoform revealed augmented ncBAF complex interaction, while exhibiting decreased binding of auxiliary proteins, including SPEN, BRCA2, and CHD9. Additionally, integrative multi-omics analysis identified a ncBAF complex-bound gene quartet on chromosome 1 with higher expression levels and more accessible chromatin in SF3B1MUT CLL. Finally, Cancer Dependency Map analysis and BRD9 inhibition displayed BRD9 dependency and sensitivity in cell lines and primary CLL cells. In conclusion, spliceosome dysregulation caused by SF3B1 mutations leads to multiple ASEs and an altered ncBAF complex interactome, highlighting a novel pathobiological mechanism in SF3B1MUT CLL.
Keywords: Phosphoproteins; fosfoproteiny; alternativní sestřih; mutace; Transcription Factors; sestřihové faktory; transkripční faktory; chronická lymfatická leukemie; Mutation; Alternative Splicing; Humans; Leukemia, Lymphocytic, Chronic, B-Cell; RNA Splicing Factors; proteiny obsahující bromodoménu; restrukturace chromatinu; Bromodomain Containing Proteins; Chromatin Assembly and Disassembly; lidé; spliceozomy; Spliceosomes